A GED no TCE-PB: representações sociais de seus usuários - Costa, Ingrid Biermann de Azevedo (2014)
Identify the GED user s social representations in TCE-PB, by tracing the user s profile and reconstructing the deployment process. The approach used was qualitative and quantitative, using the theory of social representations and discourse of the collective subject method. There were used as technical procedures the literature research and fieldwork procedures. Data were collected through the application of mixed questionnaires sent by mail or delivered by hand to the TCE-PB server s that work in the departments of management municipal auditory I and II. This study found that the GED has improved the daily executions tasks and work routines, required less time and effort to fulfill the goals and that users are satisfied with the current conditions. Even brought negative evidences that need to be improved, such as dissatisfaction with the network speed and with the functionality and information foment to SAGRES system, as well as the possibility that current working conditions may affect health.